Strategies for Religious Education for Children in the Families of Converts in Pundu Village, Cempaga Hulu District - Tia Hafizah; Abdullah Abdullah; Saiful Lutfi (Edusoshum : Journal of Islamic Education and Social Humanities, 2026)
This research aims to examine and describe how religious education strategies are applied to children in convert families, with the research location in Pundu Village, Cempaga Hulu District, East Kotawaringin Regency. This research uses a descriptive qualitative method by utilizing two types of data sources: primary data and secondary data. To obtain the data, this research uses three techniques: interviews, observations, and the collection of supporting documents. The subjects in this study are 4 Muslim convert families residing on Jalan Sendong T. These four families were selected based on the criteria of having embraced Islam for at least 5 years and having children aged up to 20 years. From the research results, it was found that religious education for children in convert families is more often carried out thru habituation and direct exemplification by the parents, especially in the practice of obligatory prayers. The habituation of the five daily prayers has become one of the most frequently used strategies by parents to shape their children's religious character from an early age. In addition, children's involvement in Islamic educational institutions such as pesantren, TPA, or madrasah also strengthens their understanding and practice of Islamic values. Overall, this research shows that the families of converts play a significant role as the primary educational institution for children, both in instilling religious values, building Islamic identity, and shaping a religious character that develops gradually and continuously.